The politics of justice in European private law / Hans-W. Micklitz. - Micklitz, Hans-W (Cambridge studies in European law and policy., 2018)
The Politics of Justice in European Private Law intends to highlight the differences between the Member States' concepts of social justice, which have developed historically, and the distinct European concept of access justice. Contrary to the emerging critique of Europe's justice deficit in the aftermath of the Euro crisis, this book argues that beneath the larger picture of the Monetary Union, a more positive and more promising European concept of justice is developing. European access justice is thinner than national social justice, but access justice represents a distinct conception of justice nevertheless. Member States or nation states remain free to complement European access justice and bring to bear their own pattern of social justice.